TINGKAT OKUPASI DAN PERUBAHAN TEKNOLOGI ARTEFAKTUAL DI KOMPLEKS GUA PRASEJARAH BELLAE, KAB. PANGKEP, SULAWESI SELATAN - nfn Supriadi (Tumotowa, 2018)
Once period residential caves in South Sulawesi is a period play of important role in the framing national history. The study has been done indicating that it’s period has a long time range between 30,000 BP - 1500 BP. The time range allows residential and occupational repetition in one place , either by the same kind of man as well as by different kinds of people. Prehistoric cave complex Bellae is an area that has been inhabited or occupational evidence ever undertaken by humans .The purpose of this study is to observe at the occupational level of each layer of culture that has ever happened in the Prehistoric Caves Complex Bellae. Three caves were used as  samples to do the excavation which represents the amount of 22 caves. The selection was made based on the consideration of the location of the cave , the cave shape, and surface findings . Excavations carried out by using a box model with a deepening technique using spit .The results of research showed that human occupation in Prehistoric Caves Complex Bellae the most intense occurred in  the  middle layer of culture. Displacement of each layer of culture , based on the findings of  kitchen waste is always decreasing occupation .  Food  gathering  system  utilizing  the surrounding environment of  the marine environment, both  freshwater and salty.  The  food  gathering  was  influenced  by  season.   From  the  results  of  the  excavation  is  also  seen  that prior  to human consumption of shellfish , the protein source is derived  from small  animals . Changes  in  the cultural layer  then accompanied  by artefaktual  changes. The  most  obvious artifacts are  finding  pottery the younger cultural layers.